2014
DOI: 10.1080/2093761x.2014.901931
|View full text |Cite
|
Sign up to set email alerts
|

A review study on the application of the fibre optic daylighting system in Malaysian buildings

Abstract: As a developing country, Malaysia requires innovation to keep abreast of the rapid growth of technology to meet the highly demanding energy consumption. The application of daylighting systems especially by fibre optics is very limited, due to the absence of relevant knowledge and the lack of understanding of the system requirements and potentials, particularly the technology of illuminating enclosed spaces which are totally surrounded by internal walls (opaque). Thus, the aim of this literature review is to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Christopher (2009) suggested the fiber optic daylighting system (FODS) as a viable solution. However, the application of FODS was found to be limited in this region because of the inconstancy of sky conditions (Abdul-Rahman and Wang, 2010;Munaaim et al, 2014aMunaaim et al, , 2014b. Furthermore, studies have shown that shading devices remain under research in this region due to constraints in sunlight quantity, i.e., direct and diffused sunlight (Al-Tamimi and Fadzil, 2011;Lim et al, 2013;Lim and Heng, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Christopher (2009) suggested the fiber optic daylighting system (FODS) as a viable solution. However, the application of FODS was found to be limited in this region because of the inconstancy of sky conditions (Abdul-Rahman and Wang, 2010;Munaaim et al, 2014aMunaaim et al, , 2014b. Furthermore, studies have shown that shading devices remain under research in this region due to constraints in sunlight quantity, i.e., direct and diffused sunlight (Al-Tamimi and Fadzil, 2011;Lim et al, 2013;Lim and Heng, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These systems have a similar function to that of SLs, which utilize direct and diffused sunlight for a light tube, whereas only direct sunlight is used in FODSs. However, both of these systems have limitations, i.e., they require clear skies and a continuous supply of sun rays during the day to function (Munaaim et al, 2014a). Christopher (2009) indicated that incorporating a lighting strategy into natural light remained a complicated procedure.…”
Section: Innovative Daylighting Systems (Ids)mentioning
confidence: 99%
“…The application of solar energy to various types of HVAC systems proved its huge potential for reducing energy usage. However, solar radiation is a highly time-dependent energy resource and it does not always meet the building demand (Munaaim et al, 2014;Al-Obaidi et al, 2017). This problem can be addressed by storing and releasing thermal energy according to building load (Aminuddin and Rao, 2008;Sulaiman, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In reality, these studies have indicated the presence of heat during light transfer. Munaaim et al [5,15] reviewed and tested Parans SP3 under Malaysian sky conditions. However, all these studies did not determine the amount of heat generated from this system.…”
Section: Introductionmentioning
confidence: 99%
“…However, these systems reduce light distribution as the depth of a room increases. Drawbacks related to sky conditions, such as glare, excessive brightness and heat, are also observed; moreover, arranging wires in light pipe systems is difficult [4,5].…”
Section: Introductionmentioning
confidence: 99%